Illegal Trade of Traditional Alcoholic Beverage (Tuak) within the Jurisdiction of Lamandau Police Resort - Edy Conceciao, Michael; Kristanto, Kiki; Januardy, Ivans (Journal of Law, Politic and Humanities, 2025)
The illegal trade of traditional alcoholic beverage tuak in the jurisdiction of Lamandau Police Department, Central Kalimantan, reflects a complex socio-legal phenomenon, especially when local cultural practices intersect with formal legal systems. Once a cultural symbol in Dayak society, tuak has transformed into an unregulated commercial commodity, contributing to rising crime rates, public disorder, and health risks. This study employs a juridical-empirical and descriptive-analytical approach to examine the effectiveness of law enforcement against illegal tuak distribution. Findings indicate that weak regulatory oversight, the absence of specific local regulations, and strong cultural acceptance are key obstacles in controlling its spread. This article recommends the establishment of a Local Regulation (Peraturan Daerah) grounded in restorative justice, cross-sectoral collaboration, and community-based educational strategies rooted in local wisdom to address the issue comprehensively.